HARMONISASI IMPLEMENTASI PERJANJIAN INTERNASIONAL DI INDONESIA: KAJIAN PUSTAKA TERHADAP PENGARUH RATIFIKASI TRAKTAT GLOBAL TERHADAP SISTEM HUKUM NASIONAL - Gunawan Widjaja; Januar Agung Saputera (INTELIGENSIA MEDIA, 2025)
This study discusses the harmonisation of international agreement implementation in Indonesia by highlighting the influence of global treaty ratification on the national legal system. Through a literature review, this study examines the ratification process, challenges faced, and implications for regulatory reform and national legal practice. The findings reveal that the ratification of global treaties encourages the updating and adaptation of legislation to align with international standards; however, this process often faces obstacles such as differences in legal systems, local cultural values, and domestic political dynamics. The harmonisation process requires close collaboration between state institutions, strong political will, and public involvement to ensure that ratification has a positive impact on justice, development, and national legal sovereignty. It is concluded that the success of harmonisation goes beyond legislative changes and lies in its actual implementation and substantive benefits for society.